THE ROLE OF PARENTS IN SUPPORTING YOUNG CHILDREN’S BILINGUALISM - Kosimov Anvar, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
This article examines the critical role that parents play in the bilingual development of young children, focusing on strategies like the OPOL approach and the challenges they face in maintaining bilingualism. Based on interviews and surveys, the article highlights the importance of consistency, cultural reinforcement, and creating a linguistically rich environment to support balanced language acquisition. The findings also emphasize the potential obstacles posed by dominant language environments and parental proficiency in both languages, while underscoring the long-term benefits of parental involvement in fostering bilingualism and bicultural identity. Keywords: Parental involvement, bilingualism, language acquisition, early childhood, language development, home environment, heritage language